RETRACTED: Dual-phenotype hepatocellular carcinoma: correlation of MRI features with other primary hepatocellular carcinoma and differential diagnosis - Zhang, Liqing; Chen, Jing; Lai, Xufeng; Zhang, Xiaoqian; Xu, Jianfeng (Frontiers in Oncology, 2024)
Objectives: Dual-phenotype hepatocellular carcinoma(DPHCC) is a rare subtype of hepatocellular carcinoma characterized by high invasiveness and a poor prognosis. The study aimed to compare clinical and magnetic resonance imaging (MRI) features of DPHCC with non-DPHCC and intrahepatic cholangiocarcinoma (ICC), exploring the most valuable features for diagnosing DPHCC.Methods: A total of 208 cases of primary liver cancer, including 27 DPHCC, 113 non-DPHCC, and 68 ICC, who undergone gadoxetic acid-enhanced MRI, were enrolled in this study. The clinicopathologic and MRI features of all cases were summarized and analyzed. Univariate and multivariate logistic regression analyses were conducted to identify the predictors. Kaplan-Meier survival analysis was used to evaluate 1-year and 2-year disease-free survival (DFS) and overall survival (OS) rates in the cohorts.In the multivariate analysis, absence of tumor capsule (P=0.046; OR=9.777), persistent enhancement (P=0.006; OR=46.941), arterial rim enhancement (P=0.011; OR=38.211), and target sign on DWI image (P=0.021; OR=30.566) were identified as independently significant factors for distinguishing DPHCC from non-DPHCC. Serum alpha-fetoprotein (AFP) >20μg/L (P=0.036; OR=67.097) and hepatitis B virus (HBV) positive (P=0.020; OR=153.633) were independent significant factors for predicting DPHCC compared to ICC. The 1-year and 2-year DFS rates for patients in the DPHCC group were 65% and 50%, respectively, while those for the non-DPHCC group were 80% and 60%, and for the ICC group were 50% and 29%. The 1-year and 2-year OS rates for patients in the DPHCC group were 74% and 60%, respectively, while those for the non-DPHCC group were 87% and 70%, and for the ICC group were 55% and 37%. Kaplan-Meier survival analysis revealed significant differences in 1-year and 2year OS rates between the DPHCC and non-DPHCC groups (P = 0.030 and 0.027) as well as between the DPHCC and ICC groups (P = 0.029 and 0.016).: In multi-parameter MRI, combining the assessment of absence of tumor capsule, persistent enhancement, arterial rim enhancement, and target sign on DWI image with clinical data such as AFP > 20μg/L and HBV status may support in the diagnosis of DPHCC and differentiation from non-DPHCC and ICC. Accurate preoperative diagnosis facilitates the selection of personalized treatment options.